Sharing Economy: Dynamic General Equilibrium Effects - Eva Nalbach (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Developments in digital technologies enabled the emergence and rapid growth of the sharing economy predicted to account for up to 5% of EU GDP in coming years. This paper contextualises these developments within a dynamic two sector model of the economy and analyses the effects of efficiency gains in the sharing sector on growth, income distribution and employment. We identify three sources of technological progress in the sharing sector and find that an expansion of this sector, in line with recent predictions, will lead to modest GDP growth and declines in both wage share and employment, if sharing is organised by profit maximising firms. We compare this solution to a case where households organise sharing directly and find that the sharing sector will be larger under the same technological conditions in the latter case.
Keywords: O41; E10; J2; 330; Neoclassical Growth Model; Two Sector Growth Model; Technological Change; Macroeconomic Model; Aggregative Model; GDP; Sharing Economy; Wage Share; Employment